Selective breeding for endurance running capacity affects cognitive but not motor learning in rats - Wikgren, Jan; Mertikas, Georgios G.; Raussi, Pekka; Tirkkonen, Riina; Äyräväinen, Laura; Pelto-Huikko, Markku; Koch, Lauren G.; Britton, Steven L.; Kainulainen, Heikki (Physiology & behavior, 2012)
The ability to utilize oxygen has been shown to affect a wide variety of physiological factors often considered beneficial for survival. As the ability to learn can be seen as one of the core factors of survival in mammals, we studied whether selective breeding for endurance running, an indication of aerobic capacity, also has an effect on learning. Rats selectively bred over 23 generations for their ability to perform forced treadmill running were trained in an appetitively motivated discrimination-reversal classical conditioning task, an alternating T-maze task followed by a rule change (from a shift-win to stay-win rule) and motor learning task. In the discrimination-reversal and T-maze tasks, the high-capacity runner (HCR) rats outperformed the low-capacity runner (LCR) rats, most notably in the phases requiring flexible cognition. In the Rotarod (motor-learning) task, the HCR animals were overall more agile but learned at a similar rate with the LCR group as a function of training. We conclude that the intrinsic ability to utilize oxygen is associated especially with tasks requiring plasticity of the brain structures implicated in flexible cognition. ► Aerobic capacity correlates positively with cognitive abilities. ► It is not known whether this is due to acquired or innate aerobic capacity. ► We trained rats bred for endurance running capacity in tasks requiring flexible cognition. ► Rats with intrinsically high running capacity outperformed those with low capacity.